Backyard poultry farming ensured livelihood/food security in NW-Himalaya during Covid-19: Success story - Muruganandam, M; Bihari, Bankey (Indian Farming, 2022)
The participatory research and demonstration of backyard poultry farming of Kroiler and Vanaraja birds conducted under the Farmers FIRST Project proved to be an economically viable rural enterprise and farming avenue that ensures food/nutritional and livelihood security in Himalayan foothill watersheds. The backyard dual-purpose poultry farming was found to be potential for scavenging since the poultry birds fed on the left-over grains in the farm fields during daytime and farmers could increase the farm bio-resource flow by 65%. The intervention improved the nitty-gritty understanding of the poultry farming with which farmers could enhance the profit as liquid money besides improving the nutritional status of the family members. The intervention has now become a promising rural enterprise that could tackle the hardship imposed by the ongoing COVID-19 pandemic and climatic change scenarios.